Kontrola procesu biologicznego oczyszczania ścieków przemysłowych z wykorzystaniem respirometrycznych pomiarów in-situ w komorach osadu czynnego = Biological control of industrial wastewater treatment using in-situ respirometric measuring of activated sludge - Głodniok, Marcin; Zdebik, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article describes the results of the analysis carried out in an industrial wastewater treatment plant. Analysis was performed using equipment purchased under the grant "MOWITEGRAC". Measurements of respiratory activity of activated sludge were made by portable respirometer Bioscope. Analyses were carried out directly in the chambers of activated sludge. The results of the analysis indicated a high load of pollution in sewage and possible toxic influent.
Keywords: respirometria; osad czynny; aktywność oddechowa; respirometry; activated sludge; oxygen